“No More Insecurities”: New Alternative Masculinities' Communicative Acts Generate Desire and Equality to Obliterate Offensive Sexual Statements - Zubiri-Esnaola, Harkaitz; Gutiérrez-Fernández, Nerea; Guo, Mengna (Frontiers in Psychology, 2021)
To justify attraction to Dominant Traditional Masculinities (DTM) and lack of attraction to non-aggressive men, some women defend opinions such as “there are no frigid women, only inexperienced men”. Such statements generate a large amount of sexual-affective insecurity in oppressed men and contribute to decoupling desire and ethics in sexual-affective relationships, which, in turn, reinforces a model of attraction to traditional masculinities that use coercion, thus perpetuating gender-based violence. New Alternative Masculinities (NAM) represent a type of masculinity that reacts to reverse such consequences with communicative acts, in which they state that women who support such discourses have never met a NAM man or have never experienced a successful sexual-affective relationship where passion, love, desire, and equality are all included. This article presents data analyzing these communicative acts (exclusory and transformative; language employed and consequences) to ultimately find the key to NAM communication that would contribute to changing attraction patterns. The data was collected using communicative daily life stories of three heterosexual white men and one heterosexual white woman, between the ages of 30 and 40. Findings emphasize the importance of self-confidence manifested by NAM men when communicating about sex and facing these offensive mottos in the presence of other men and women. Findings also demonstrate that supportive egalitarian relationships encourage the emergence of self-confidence in NAM men and that NAM men's self-confident communicative acts foster healthy relationships and obliterate coercive ones.